ANALYSES OF DIFFICULTIES AND OBSTACLES IN THE FINAL REPORT WRITING OF THE STUDENTS AT BUSINESS ADMINISTRATION DEPARTMENT AT STATE POLYTECHNIC OF SRIWIJAYA - Wasitoh Meirani; Mihammad Erwin; Suroso -; Ayu Puspasari (HOLISTICS, 2017)
The aims of research  are to know the difficulties and obstacles faced by the students atBusiness Administration Department in the academic year 2014/2015 of State Polytechnic of Sriwijaya in writing  final report and to know the steps that can be done to resolve them. The research method used in the research is the triangulation  consisting of  questionnaires, interviews, and document analyses. The findings show that most students experienced difficulties and obstacles in the writing of the final report. Most of the difficulties perceived by students are the difficulties of writing the background, the scope of the problem, the benefits of research, and research purposes. The barriers faced by students include obstacles that come from the students themselves, from the advisors at Business Administration Department, from Business Administration Department, and from the subjects of research.